CULTIVATING IMAGINATION IN EDUCATION PROCESS: CONTEXT OF PRIMARY TEACHERS’ OPINIONS - Bilbokaitė, Renata; Bilbokaitė-Skiauterienė, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The importance of imagination in the process of education is unquestionable - by developing the ability to create and retain images, sounds, feelings as a reflection of one’s thoughts, the basis of thinking is constructed. All this helps students to discover and create something completely new, solve problems, move to other spaces, understand others.The article theoretically substantiates the importance of developing children’s imagination and empirically reveals the opinion of primary school teachers about the aspects of developing imagination and visualization skills in the educational process.The written questionnaire study was carried out in January – July of 2020. The study involved 390 primary school teachers which shows the validity of the data and reflects the opinion of the majority of Lithuanian primary school teachers in the context of the analysed object. The data were processed using descriptive statistics (frequency) and analytical statistics (Mann Whitney U Test).The results of the research reveal that the imagination of primary school students is usually developed through fairy tales, character role plays, and in language teaching subjects, images are usually conveyed through verbal codes. In Maths, language teaching and Science lessons, students usually depict fantastic objects, diagrams, tables and charts, draw folk symbols, and produce visual instruments.